High kick to sprinter's lunge - Walker, M. (Strength and Conditioning Journal, 2013)
This column provides a detailed description with figures to demonstrate the high kick to sprinter's lunge. The high kick to sprinter's lunge is a dynamic flexibility exercise that can be used as part of a warm-up program to provide active stretching for the lower extremities and to improve hip mobility.